use of dietary supplement in Iraq - S. Shihab, Sami; M. Jawad, Haidar; nasir, zahraa matheel; M. Jasim, Eman (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Dietary supplementation is a common strategy to achieve a specific health status or performance benefit. The aim of this study was to describe the use of dietary supplement in Iraqi genders. Patients and Methods: several questions on dietary supplement use were asked as a part of single performed on 112 female and 247 women aged 35–74 years in 2021 .n = 359) ,reported the frequency and prevalence of supplement use by sex and type of supplement . Results: the mean percentage of dietary supplement use varied among female and men. Use was higher in women than in men. Vitamins, minerals were the predominant types of supplements reported, but there were striking differences between genders. Vitamins, particularly D, C, were the most frequently used ingredients by both genders. Herbals use in female more than male. Conclusions: This study indicates that there are wide variations in supplement use in Iraq, which may affect individual and population nutrient intakes. The results underline the need to monitor consumption of dietary supplements, as well as to evaluate the risks and benefits. Keywords: Abstract Background: Dietary supplementation is a common strategy to achieve a specific health status or performance benefit. The aim of this study was to describe the use of dietary supplement in Iraqi genders. Patients and Methods: several questions on dietary supplement use were asked as a part of single performed on 112 female and 247 women aged 35–74 years in 2021 .n = 359) ,reported the frequency and prevalence of supplement use by sex and type of supplement . Results: the mean percentage of dietary supplement use varied among female and men. Use was higher in women than in men. Vitamins, minerals were the predominant types of supplements reported, but there were striking differences between genders. Vitamins, particularly D, C, were the most frequently used ingredients by both genders. Herbals use in female more than male. Conclusions: This study indicates that there are wide variations in supplement use in Iraq, which may affect individual and population nutrient intakes. The results underline the need to monitor consumption of dietary supplements, as well as to evaluate the risks and benefits. Keywords: Dietary supplements type; Iraq; vitamins; minerals, herbals.